THE RELATIONSHIP BETWEEN THE DEVELOPMENT OF RICKETS AND THE LEVEL OF 25 (OH) D IN THE BLOOD - Rasulova Nadira Alisherovna; Rasulov Alisher Sobirovich (Journal Park Publishing, 2024)
Despite the fact that rickets has been known since ancient times, this problem remains relevant today. As a result of the study, 28.9% of children had signs of rickets. Of the factors on the part of the child, these were the low content of 25(OH)D3 in the blood serum of children (78.3%), the lack of prevention of rickets with vitamin D in the 1st year of life (68.9%), frequent acute respiratory viral infections (49.4 %), insufficient exposure to fresh air for less than 20 minutes (38.6%), time of birth of the child (autumn-winter period) (32.4%), perinatal factors (32.1%), birth weight of the child over 35,000 g (24.7%). The main factors on the part of mothers are the lack of vitamin D intake during pregnancy (85.2%), malnutrition during pregnancy (59.0%), iron deficiency anemia during pregnancy (62.0%), housewives (48.5%), young age of the mother during the 1st pregnancy (54.1%) and complicated childbirth (47.8%), while toxicosis of pregnant women accounted for only 13.7%.
Keywords: rickets, risk factors, serum 25 (OH) D3, children, biochemical parameters of blood, Student's criterion.